Zombification in Europe in times of pandemic - Luc Laeven; Glenn Schepens; Isabel Schnabel (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Large-scale government and central bank interventions in the context of the COVID-19 crisis have reinvigorated the debate on the threat of a zombification of the economy if unviable firms are kept alive. This column surveys the existing literature and argues that the COVID-19 crisis is very different from previous experience. It proposes a number of policy actions that can prevent a zombification of the economy.
Keywords: 330